En la búsqueda de la adaptación y la resistencia: innovaciones biológicas en el cultivo de trigo en México, 1909-1941 - Rivas Sada, Eva Luisa (El Colegio de México, A.C., 2020)
This article is centered on the phenomenon of biological innovations in Mexican wheat cultivation during the period between 1909 and 1941, which it considers to represent the first stage of scientific agriculture in the country. Opening with a brief theoretical discussion on what is understood to be biological innovation, as well as its role in the expansion of commercial agriculture, it puts forward a general characterization and periodization of commercial agriculture with a scientific basis in Mexico. The analysis begins with a taxonomic description of Mexico’s commercial wheat varieties and their relationship with both productive-nutritional uses and the primary local agricultural and economic problems. It then analyzes the different government programs that, in various stages and using different strategies, promoted selective breeding. This led to the development of new wheat varieties aimed at increasing and expanding productivity, as well as making the crop plague-resistant and better-adapted to the ecological diversity of the country’s most important agricultural regions. It pays close attention to the “red queen effect” as one of the most important phenomena in terms of the limits of scientific research into agronomics in Mexico and sheds light on aspects that allow us to better understand lesser-known agrobiological phenomena in Mexico in the first half of the 20th Century. The article closes by summarizing the achievements and unresolved problems during this period, which was the initial stage and direct antecessor of the Green Revolution in Mexico’s agricultural sector.